Pengaruh IPM dan Kemiskinan Terhadap Pertumbuhan Ekonomi Provinsi Jatim - Dwi Maulidia Anggraeni; Tony Seno Aji (Universitas Negeri Surabaya, 2022)
The highest rate of economic growth in Java is owned by the East Java Province, but on the other hand the East Java Province also has the highest number of poor people in Indonesia. This condition can be analyzed that in essence, efforts to increase economic growth must be accompanied by efforts to increase HDI and poverty alleviation. The purpose of this study is to analyze whether the implementation of HDI and poverty have a positive impact on economic growth in East Java Province partially and simultaneously. The type of research used in this research is quantitative with the ex post de facto method. This study uses panel regression analysis with the REM model. The results of this study are 1). HDI has a positive impact on economic growth in East Java Province in 2019-2021, 2). Poverty has a negative impact on economic growth in East Java Province in 2019-2021, and 3). HDI and poverty have a simultaneous positive impact on economic growth in East Java Province in 2019-2021.